2017
DOI: 10.5194/angeo-35-923-2017
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and differences in morphology and mechanisms of the <i>fo</i>F2 and TEC disturbances during the geomagnetic storms on 26–30 September 2011

Abstract: Abstract. This study presents an analysis of the groundbased observations and model simulations of ionospheric electron density disturbances at three longitudinal sectors (eastern European, Siberian and American) during geomagnetic storms that occurred on 26-30 September 2011. We use the Global Self-consistent Model of the Thermosphere, Ionosphere and Protonosphere (GSM TIP) to reveal the main mechanisms influencing the storm-time behavior of the total electron content (TEC) and the ionospheric F2 peak critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 76 publications
1
13
0
3
Order By: Relevance
“…Thus, the problem of theoretical justification of the fact that the most favorable conditions for positive after-effects of geomagnetic storms exist in spring is still unsolved. It should again be noted that the previous model calculations of ionospheric responses to magnetic storms Klimenko et al, 2017Klimenko et al, , 2018 have shown that a positive after-storm effect can be observed both in fall and in spring.…”
Section: After-storm Effect Phase (Days 3-5)mentioning
confidence: 81%
See 3 more Smart Citations
“…Thus, the problem of theoretical justification of the fact that the most favorable conditions for positive after-effects of geomagnetic storms exist in spring is still unsolved. It should again be noted that the previous model calculations of ionospheric responses to magnetic storms Klimenko et al, 2017Klimenko et al, , 2018 have shown that a positive after-storm effect can be observed both in fall and in spring.…”
Section: After-storm Effect Phase (Days 3-5)mentioning
confidence: 81%
“…The previous results Klimenko et al, 2017Klimenko et al, , 2018 offered no insight into the question of whether the after-storm effects characterize the September 26, 2011 and March 17, 2015 geomagnetic storms or they are typical of all geomagnetic storms. To answer this question, we have developed a special method of statistical analysis of ionospheric responses to geomagnetic storms, which is based on Irkutsk (52° N, 104° E) and Kaliningrad (54° N, 20° E) ionosonde data.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is found that the previous studies showcased the hemispheric asymmetry in ionospheric responses irrespective of daytime or nighttime and mostly the large scale spatiotemporal features up to the recovery phase have been discussed that show all kinds of effects including PPEF, TADs, and composition changes and disturbance dynamo de Abreu et al, 2010;Klimenko et al, 2017;Luo et al, 2016;Yao et al, 2016;Yiğit et al, 2016;Yue et al, 2016). It is found that the previous studies showcased the hemispheric asymmetry in ionospheric responses irrespective of daytime or nighttime and mostly the large scale spatiotemporal features up to the recovery phase have been discussed that show all kinds of effects including PPEF, TADs, and composition changes and disturbance dynamo de Abreu et al, 2010;Klimenko et al, 2017;Luo et al, 2016;Yao et al, 2016;Yiğit et al, 2016;Yue et al, 2016).…”
Section: Discussionmentioning
confidence: 99%